The Effect of Participatory Budgeting, Internal Control Systems, Ethical Behavior of Leaders and Organizational Culture on Public Accountability - Sholihin, Muhammad Khairus; Pituringsih, Endar; Surasni, Ni Ketut (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
This research aims to test and obtain empirical evidence regarding the effect of participatory budgeting, internal control systems, ethical behavior of leaders, and organizational culture on public accountability. This research was conducted on all NGOs in West Nusa Tenggara Province, using a purposive sampling technique with sample used by 102 people and using multiple linear regression. The results of this study indicate that participatory budgets have a positive and significant effect on accountability, the internal control system has a positive and significant effect on public accountability, the ethical behavior of leaders has a positive and significant effect on public accountability, organizational culture has a positive but insignificant effect on public accountability.